2017
DOI: 10.1136/bmjopen-2017-017585
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and healthcare costs of persistent postoperative pain following lumbar spine surgery in the UK: a cohort study using the Clinical Practice Research Datalink (CPRD) and Hospital Episode Statistics (HES)

Abstract: ObjectiveTo characterise incidence and healthcare costs associated with persistent postoperative pain (PPP) following lumbar surgery.DesignRetrospective, population-based cohort study.SettingClinical Practice Research Datalink (CPRD) and Hospital Episode Statistics (HES) databases.ParticipantsPopulation-based cohort of 10 216 adults who underwent lumbar surgery in England from 1997/1998 through 2011/2012 and had at least 1 year of presurgery data and 2 years of postoperative follow-up data in the linked CPRD–H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 29 publications
0
56
0
1
Order By: Relevance
“…Lumbar spine surgeries are commonly performed in patients with chronic low back pain . The International Association for the Study of Pain (IASP) define Failed Back Surgery Syndrome (FBSS) as Lumbar spinal pain of unknown origin either persisting despite surgical intervention or appearing after surgical intervention for spinal pain originally in the same topographical location .…”
Section: Introductionmentioning
confidence: 99%
“…Lumbar spine surgeries are commonly performed in patients with chronic low back pain . The International Association for the Study of Pain (IASP) define Failed Back Surgery Syndrome (FBSS) as Lumbar spinal pain of unknown origin either persisting despite surgical intervention or appearing after surgical intervention for spinal pain originally in the same topographical location .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is a considerable proportion of patients who experience recurrent or remaining pain following initial spine surgery, ranging from 3 to 34% at follow-up between 6 and 24 months after surgery, and 5 to 36% upon long-term evaluation (> 2 years) [3,4]. A recent populationbased cohort study in England reported that over the period 2007-2012 on average 20.8% of lumbar surgery patients experienced persistent post-operative pain [5]. Unsatisfactory results after spinal surgery are often referred to as "failed back surgery syndrome" (FBSS), but this term has been criticised because it unilaterally puts the blame on the operation as the cause of the problem, while the aetiology is much more complex and often multifactorial [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…6 Unfortunately, significant persistent pain, functional limitations, diminished HRQoL, and narcotic use can affect up to one third of patients post-surgery. [7][8][9] More specifically, there is evidence to suggest that approximately 30% of patients do not reach minimal clinical important change in disability, pain or quality of life after 1 year post-surgery. [10][11][12] Further, a recently published large population-based study identified that more than 40% of patients undergoing fusion for SLSS remain long-term opioid users.…”
Section: Introductionmentioning
confidence: 99%